Theoretical Basis of the Process of Obtaining Granular Magnesium Lime-Ammonium Nitrate with the Addition of Dolomites of Uzbekistan - Nabiev A. A., Alikhonova Z. S., Rizaev Sh. N., Talipova H. S. (International Journal of Modern Agriculture, 2021)
The degree of carbonation of lime-ammonium nitrate samples obtained after the addition of dolomite flour to ammonium nitrate solution, chemical composition, porosity of fertilizer grains, melting times, viscosity, grain strength, grain diesel oil absorption, modification changes, crystalline grains . The initial decomposition temperature and the activity energy of the samples obtained were determined by heating in the range of 25 to 300 S0. The thermal stability of magnesium lime-ammonium nitrate grains to heating-cooling cycles of 20â†”ï¸60 Â° C was studied. Radiographs of primary products and magnesium-lime ammonium nitrate were studied.